Corporate Social Responsibility: A Case Study of Microsoft Corporation - Sehgal, Gaurav; Kee, Daisy Mui Hung; Low, An Rou; Chin, Yan Sin; Woo, Eunice Mun Yee; Lee, Pei Fern; Almutairi, Farah (AIBPM Publisher, 2020)
The paper intends to examine corporate social responsibility in Microsoft Corporation. Microsoft Corporation is committed to Corporate Social Responsibility (CSR) with the belief that CSR helps to improve the reputation and image of an organization. On this matter, the successful technology company, Microsoft Corporation has done significant initiatives on its CSR programs. One of the many reasons behind this success is their commitment towards sustainability as well as their commitment to all stakeholders. The paper discusses the various initiatives Microsoft Corporation have done for CSR. The paper concludes with some suggestion and recommendation.